Protein Digestibility, Nitrogen Retention, and Meat Protein Mass of Broiler chickens Fed on Mulberry Leaves Fermented with Rumen Liquid - . Mirnawati; B. Sukamto; V. D. Yunianto (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2013)
The aim of the experiment was to determine the optimal levels in the utilization of mulberry leaves fermented with rumen liquid as well as unfermented mulberry leaves, based on its effects on protein digestibility, nitrogen retention, and protein mass of broiler chickens. One hundred CP 707 day old chicks, unsex, were randomly assigned to receive one of five treatments diets were T0 (basal diet), T1 (10% unfermented mulberry leaf), T2 (10% fermented mulberry leaf), T3 (20% unfermented mulberry leaf), and T4 (20% fermented mulberry leaf). Replication for each treatment was four so that the total experimental unit was 20 and each experimental unit consisted of five chickens. The results showed that the administration of 10% mulberry leaves increased the digestibility of protein fermentation, but had no effects on nitrogen retention and protein mass of meat.